Jasmonate signaling in plant stress responses and development - active and inactive compounds - Wasternack, Claus; Strnad, Miroslav (New biotechnology, 2016)
Jasmonates (JAs) are lipid-derived signals mediating plant responses to biotic and abiotic stresses and in plant development. Following the elucidation of each step in their biosynthesis and the important components of perception and signaling, several activators, repressors and co-repressors have been identified which contribute to fine-tuning the regulation of JA-induced gene expression. Many of the metabolic reactions in which JA participates, such as conjugation with amino acids, glucosylation, hydroxylation, carboxylation, sulfation and methylation, lead to numerous compounds with different biological activities. These metabolites may be highly active, partially active in specific processes or inactive. Hydroxylation, carboxylation and sulfation inactivate JA signaling. The precursor of JA biosynthesis, 12-oxo-phytodienoic acid (OPDA), has been identified as a JA-independent signaling compound. An increasing number of OPDA-specific processes is being identified. To conclude, the numerous JA compounds and their different modes of action allow plants to respond specifically and flexibly to alterations in the environment.
Keywords: Plants; biotechnologie; signální transdukce; Oxylipins; regulátory růstu rostlin; oxylipiny; Models, Biological; Signal Transduction; regulace genové exprese u rostlin; rostliny; Stress, Physiological; Fatty Acids, Unsaturated; biologické modely; Plant Growth Regulators; Gene Expression Regulation, Plant; Biotechnology; Cyclopentanes; cyklopentany; nenasycené mastné kyseliny; fyziologický stres